THE HISTORICAL RETROSPECTIVE FORMING TOWN- SATELLITES OF KIEV AND DISSEMINATION SUBURBANIZATION PROCESSES IN THE KYIV REGION - Клюйко, Тетяна (Human Geography Journal, 2014)
The article analyzes historical and geographical features of the formation of urban communities around the city of Kiev. The reasons of settlements individual identity are emphasis, their functions and spheres of influence are determined. The interrelation of town- satellites to the main city and their further development influence of the city-core are characterized. The following elements as proximity and availability of communication with the city-core, low population density, monofunctional space are determined like satellite city identify. The influence of the industrial revolution and the development of Scientific Progress to dissemination suburbanization processes are shown.